Koneksi Politik Dan Praktik Manajemen Laba Riil: Studi Pada Industri Keuangan Di Indonesia - Supatmi Supatmi; Lilis Handayani (Jurnal Akademi Akuntansi, 2022)
The aim of the research is to find empirical evidence of the impact of political ties on the management of actual earnings in the Indonesian financial industry. Earnings management in this study is measured by real earnings management, namely abnormal CFO and abnormal discretionary expense, as well as the value of Allowance for Impairment Losses (CKPN). The research sample is 98 companies that are members of the financial industry listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period with a total of 294 observations. This research used the panel data regression analysis technique. The results showed that the politically connected board of commissioners had a positive effect on earnings management as measured by abnormal CFO and CKPN, but had no effect on earnings management as measured by abnormal discretionary expense. Meanwhile, the politically connected board of directors was found to have no effect on earnings management, either as measured by abnormal CFO, abnormal discretionary expense, or CKPN. This research provides additional empirical evidence that is advantagoues for several parties such as companies, investors and regulators regarding the consideration of political connected council that have a negative effect on earnings management. The results of this study support the agency theory that political connections increase agency problems through earnings management practices.